Simulasi Sistem Monitoring Link Metro Ethernet (ME) di PT Indosat Ooredoo Medan dengan Metode Doppler - Mhd Ramadhan Nainggolan; Pristiwanto Pristiwanto (JURIKOM (Jurnal Riset Komputer), 2020)
Current technological developments have been so rapid, monitoring computer networks has become a very necessary thing. Computer network connection is a fundamental thing in a computer network that cannot be used. Likewise for the Metro Ethenet network work, If a parameter is problematic then the quality of the network will be reduced and Frequently occurs the duration of Metro ethernet monitoring and access to the report report ME becomes disrupted. This Final Project I will discuss how the Metro Ethernet Link Monitoring Simulation System in PT Indosat Ooredoo with the doppler method to determine the status of the Link on Metro Ethernet uses tree topology because it only simulates 3 Metro Ethernet and also discusses Metro Ethernet performance, which analyzes simulation applications, and Metro Ethernet Link status. Metro Ethernet is one of the technological solutions for High End Market (HEM) in providing integrated solutions for voice, data and video services. Metro Ethernet network has characteristics. Based on the above problems, a system for Metro Ethernet Link monitoring simulation is needed at Indosat Ooredoo to get better results than the previous system.